Hypatia, Volume 18, no. 1, Winter 2003. Special Issue: "Feminist Philosophy and the Problem of Evil" - Cathrine Egeland (The Royal Danish Library, 2003)
Cathrine Egeland anmelder: Hypatia, Volume 18, no. 1, Winter 2003. Special Issue: "Feminist Philosophy and the Problem of Evil"